Transcription Mapping of the Kaposi’s Sarcoma-Associated Herpesvirus (Human Herpesvirus 8) Genome in a Body Cavity-Based Lymphoma Cell Line (BC-1) - Sarid, Ronit (American Society for Microbiology, 1998)
Kaposi’s sarcoma-associated herpesvirus (KSHV) gene transcription in the BC-1 cell line (KSHV and Epstein-Barr virus coinfected) was examined by using Northern analysis with DNA probes extending across the viral genome except for a 3-kb unclonable rightmost region. Three broad classes of viral gene transcription have been identified. Class I genes, such as those encoding the v-cyclin, latency-associated nuclear antigen, and v-FLIP, are constitutively transcribed under standard growth conditions, are unaffected by tetradecanoylphorbol acetate (TPA) induction, and presumably represent latent viral transcripts. Class II genes are primarily clustered in nonconserved regions of the genome and include small polyadenylated RNAs (T0.7 and T1.1) as well as most of the virus-encoded cytokines and signal transduction genes. Class II genes are transcribed without TPA treatment but are induced to higher transcription levels by TPA treatment. Class III genes are primarily structural and replication genes that are transcribed only following TPA treatment and are presumably responsible for lytic virion production. These results indicate that BC-1 cells have detectable transcription of a number of KSHV genes, particularly nonconserved genes involved in cellular signal transduction and regulation, during noninduced (latent) virus culture.